Structure of the Exile Sentence in the Hairs of the Pendants - Difar Erayer, Rafid (International Journal of Psychosocial Rehabilitation, 2020)
This research dealt with the structure of the exile sentence in the seven commentaries. It was based on Al-Zawzani’s interpretation of its suitability for the subject of the study. Par in the poetry of the seven pendants.